Cardiovascular Mortality in 10 Cohorts of Middle-Aged Men Followed-Up 60 Years until Extinction: The Seven Countries Study - Alessandro Menotti; Paolo Emilio Puddu; Anthony G. Kafatos; Hanna Tolonen; Hisashi Adachi; David R. Jacobs (Journal of Cardiovascular Development and Disease, 2023)
Objectives. To investigate mortalities from three major groups of cardiovascular diseases (CVDs) in a pooled cohort and followed up until extinction. Materials and Methods. Ten cohorts of men (N = 9063) initially aged 40–59, in six countries, were examined and followed-up for 60 years. The major CVD groups were coronary heart disease (CHD), cerebrovascular diseases (STROKE) and other heart diseases of uncertain etiology (HDUE). Results. Death rates from CHD were higher in countries with high serum cholesterol levels (USA, Finland and The Netherlands) and lower in countries with low cholesterol levels (Italy, Greece and Japan), but the opposite was observed for STROKE and HDUE, which became the most common CVD mortalities in all countries during the last 20 years of follow-up. Systolic blood pressure and smoking habits were, at an individual level, the common risk factors for the three groups of CVD conditions, while serum cholesterol level was the most common risk factor only for CHD. Overall, death rates for the pooled CVDs were 18% higher in North American and Northern European countries, while CHD rates were 57% higher in the same countries. Conclusions. Differences in lifelong CVD mortalities across different countries were smaller than expected due to the different rates of the three groups of CVD, and the indirect determinant of this seemed to be baseline serum cholesterol levels.